Analysis of colifrom bacteria of dishwasting water food stalls in Lubuk Pakam - AHMAD ILHAM; ANGELIKA; ASVIA RAHAYU; RIMAYANI; Rahmadani Sitepu (Institut Kesehatan Medistra Lubuk Pakam, 2024)
Food stalls play a role in helping fulfil daily needs by offering convenient and fast services, so people like to eat food at food stalls. If contaminated cutlery is used, those who use it may be infected with disease-causing microbes. Objective: The purpose of this study was to determine the presence of Coliform bacteria in water both before and after being used to clean food utensils in food stalls around the Medistra Institute of Health Lubuk Pakam. Methods: The method used is quantitative, as well as experimental to test water quality with applicable quality standards and describe the results of research based on literature review. Results: Of the 4 food stalls around the Medistra Institute of Health, it shows that there are 3 food stalls in the category of not meeting health requirements and 1 other food stall in the category of meeting health requirements based on the maximum number of total coliforms for piped and non-piped water 10/100 and 50/100 ml of water samples respectively in accordance with Permenkes No. 416/Per/Menkes/IX/1990. The quality of washing water (clean water) used in food stalls around the Medistra Institute of Health based on the results of laboratory tests of total Coliform, from four food stalls around the Medistra Institute of Health, 3 food stalls in the category of not meeting health requirements and 1 other food stall in the category of meeting the requirements according to Permenkes No. 416/Per/Menkes/IX/1990, concerning clean water quality for piped and non-piped water with numbers 10/100 ml and 50/100 ml of water samples. Keywords : Coliform bacteria, Escherichia coli, Dishwasting Water